The Influence of Store Atmosphere and Service Quality on Consumer Purchasing Decisions at Allbaik Chicken Sawah Lebar Bengkulu City - Ilhami, Mardhiyah Dwi; Sari, Lina Dwita (JURNAL BISNIS STRATEGI, 2024)
The aim of the research is to determine the influence of store atmosphere and service quality on consumer purchasing decisions at Allbaik Chicken Sawah Width , Bengkulu City. And to find out which factors most dominantly influence purchasing decisions. This research used quantitative methods on 150 respondents.The population used in this research were consumers in Allbaik Chicken Sawah Lebar , Bengkulu City and sampling in this research used a non-probability sampling technique. Based on the results of multiple linear regression, the regression equation form Y = 9,100 + 0.277 (X1) + 0.506 (X2) is obtained. The research results and hypothesis show that Store Atmosphere and Service Quality have a positive effect on Purchasing Decisions.